Analisis Penggunaan Fitur Vicon (Video Conference) pada E-Learning Ilmu Terhadap Kelancaran Pembelajaran Daring Di Fakultas Ilmu Komputer UPN Veteran Jawa Timur - Candra, Devilia Dwi; Jannatuzzahra, Khoirunisa; Kartika, Annisa Dita Putri; Pratiwi, Widya; Nurhayati, Eni (Journal Software, Hardware and Information Technology, 2024)
Online learning has become an integral part of higher education in today's digital era, especially following the COVID-19 pandemic. Video conferencing (Vicon) technology plays a crucial role in this transition, enabling direct interaction between teachers and students without the need for physical presence in the classroom. This study aims to analyze the use of Vicon features in the context of online learning and its impact on the smoothness of the learning process. Data were collected through a questionnaire administered to students of the Faculty of Computer Science at UPN Veteran Jawa Timur, with the System Usability Scale (SUS) method employed for calculation. The collected data were then qualitatively analyzed to determine the effectiveness of Vicon use by identifying usage patterns, obstacles faced, and student perceptions of its impact on the learning process. Analysis of the SUS scores, usage patterns, challenges, and student perceptions revealed a low average SUS value. This indicates that while Vicon facilitates direct interaction and effective material delivery, there are still significant technical obstacles and low participation rates. These findings suggest the need for improvements in the technical aspects of Vicon and strategies to increase student engagement in online learning environments.